12th International Biennale of Drawings : Sculptural Drawing - Hulten, Pontus; 12th International Biennale of Drawings, Rijeka, 1990 (Rijeka : Moderna Galerija, 1990)
Aiha, Martti ; Bajic, Mrdan ; Gegic, Mirsad ; Bjorlo, Per Inge ; Bogdanovic, Kosta ; Buren, Daniel ; Colson, Greg ; Colson, Jeff ; Dzamonja, Dusan ; Francis, Sam ; Kozaric, Ivan ; Mahoney, Gregory ; Norgaard, Bjorn ; Perry, Sarah ; Pogacnik, Marko ; Rollof, Ulf ; De Saint Phalle, Niki ; Sambolec, Dubravka ; Sarkis ; Semov, Simon ; Tapper, Kain ; Therrien, Robert ; Tinguely, Jean ; Tolaas, Sissel
12th International Biennale of Drawings : Sculptural Drawing, Moderna Galerija, (Museum of Modern Art) Rijeka, 20.12.1990 - 17.02.1991
boek